HECT E3 Ligases: A Tale With Multiple Facets - Weber, Janine; Polo, Simona; Maspero, Elena (Frontiers in Physiology, 2019)
Ubiquitination plays a pivotal role in several cellular processes and is critical for protein degradation and signalling. E3 ubiquitin ligases are the matchmakers in the ubiquitination cascade, responsible for substrate recognition. In order to achieve selectivity and specificity on their substrates, HECT E3s enzymes are tightly regulated and exert their function in a spatially and temporally controlled fashion in the cells. These characteristics made HECT E3s intriguing targets in drug discovery in the context of cancer biology.